2023
DOI: 10.3847/1538-4357/aca1c7
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Age, Metallicity, and Abundances for Disk Stars in a Simulated Milky Way

Abstract: Observations of the Milky Way’s low-α disk show that several element abundances correlate with age at fixed metallicity, with unique slopes and small scatters around the age–[X/Fe] relations. In this study, we turn to simulations to explore the age–[X/Fe] relations for the elements C, N, O, Mg, Si, S, and Ca that are traced in a FIRE-2 cosmological zoom-in simulation of a Milky Way–like galaxy, m12i, and understand what physical conditions give rise to the observed age–[X/Fe] trends. We first explore the distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 121 publications
1
4
0
Order By: Relevance
“…Our method also reproduces R birth distributions found in state-of-the-art simulations (e.g. Agertz et al 2021 ;Carrillo et al 2023 ). In contrast to Minchev et al ( 2018 ), who imposed such shifting in the peaks of mono-R birth populations in order to estimate the Milky Way's ∇[Fe / H]( τ ), here we reach a very similar configuration directly from the data, as described abo v e.…”
Section: E T H O D F O R E S T I M At I N G B I Rt H R a D I Isupporting
confidence: 53%
See 1 more Smart Citation
“…Our method also reproduces R birth distributions found in state-of-the-art simulations (e.g. Agertz et al 2021 ;Carrillo et al 2023 ). In contrast to Minchev et al ( 2018 ), who imposed such shifting in the peaks of mono-R birth populations in order to estimate the Milky Way's ∇[Fe / H]( τ ), here we reach a very similar configuration directly from the data, as described abo v e.…”
Section: E T H O D F O R E S T I M At I N G B I Rt H R a D I Isupporting
confidence: 53%
“…If R birth can be reco v ered using the observed age and [Fe / H] ( Minchev et al 2018 ;Lu et al 2022a ), as it also appears to be the case in cosmological simulations of Milky Way-like galaxy discs (Feltzing, Bowers & Agertz 2020 ), then this should have implications for all other chemical elements. Indeed, Ness et al ( 2019 ), Sharma et al ( 2022 ), andCarrillo et al ( 2023 ) (using APOGEE, GALAH , and cosmological zoom-in simulations, respectively) demonstrated that for stars in small bins of [Fe / H] and age, all other abundances had very small scatter. More recently, Hayden et al ( 2022 ) used the correlation between age, [Fe / H], and elemental abundances to estimate ages for the GALAH dataset, thus using properties of stars born at the same time and place without actually reco v ering R birth (see also He, Luo & Chen 2022 ).…”
mentioning
confidence: 99%
“…• The age-metallicity relationship is reportedly uncorrelated or anti-correlated, according to a number of studies [90][91][92][93]. However, the mass and star-formation histories of the galaxies as well as their environments affect the age-metallicity slope.…”
Section: Discussionmentioning
confidence: 99%
“…In effect, the X-ray relationship extends the range over which more reliable ages can be determined for early M dwarfs. Additional methods of age determination involving kinematics (Lu et al 2021) and abundances (Carrillo et al 2023) can also be employed to achieve results based on as many techniques as the data allow. This opportunity to determine M dwarf ages through multiple methods, or to compare the ages of each method for targets with high-quality data, holds great potential for future studies.…”
Section: The M Dwarf Activity-age Relationshipsmentioning
confidence: 99%